Review on Solar Collector for Agricultural Produce - Ahmad Fudholi; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
Among the most important components of solar energy systems, solar collectors are devices that receive solar energy and convert it into thermal energy, as most essential components of solar dryer. This review presents description and previous work performed on performances of solar air collector for agricultural produce. In addition, various solar collectors are classified and described. Solar air collectors for drying application of agricultural produce are presented and summarize. The energy and exergy efficiency of the solar air collector ranges from 28% to 62% and from 30% to 57%, respectively.